Application of stochastic dynamic programming to investigate performance of hydropower project with storage and pumped-storage system - Dhakal, Bhuban Prasad (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Application of optimization techniques for determining an optimal operating policy and maximization of expected annual energy generation for a reservoir is a major title in water resources planning and management and a key concern to all hydro developer. Stochastic Dynamic Programming (SDP) is a useful tool to understand water resources system where inherent uncertainty is associated in deriving the optimal installed capacity. Choice of inflow process assumptions for water resources system is significant for such SDP model. Among the inflow process assumptions considered in SDP models, Markov Chain First Order and independent assumptions find extensive application. Backward recursive explicit SDP model with a monthly and weekly time steps are executed to determine expected annual energy yield. The operating policy consists of maximization of reservoir release for a given inflow and storage state variables and thereby optimally deduced steady operating policy and then to estimate expected monthly and annual hydropower energy generation as a guideline for the very First years of plant operation. An under construction Ulu Jelai Hydropower Project (UJHPP) and planned Ulu Jelai Pumped-Storage Project (UJPSP) Malaysia has been used for the SDP application. Furthermore, acquisition on hydrological data on the project, review of previous studies and to explore energy generation mix, tariff patterns, trends and practices of energy consumption in the Malaysia Peninsula to determine pumping and generating hours of UJHPP and UJPSP are the other folds of the study. The expected value of annual energy generation for a monthly time step is estimated from this research work is 313 GWh and 620 GWh respectively for the UJHPP and UJPSP where as it is 323 GWh and 634 GWh from weekly time step. Revisit on the UJPSP installed capacity is felt to ascertain longer generation hours. Keywords: Stochastic Dynamic Programming, Backward Recursive, Energy Generation Mix, Pump Storage Project, Peaking Plant, Energy Tariff Patterns
Thesis (Ph.D. in Civil Engineering)--University of the Philippines, Diliman.
Keywords: Stochastic programming; Dynamic programming; Water-power.